OC-056 Viral warfare: front line defence and arming the immune system: the use of an oncolytic virus as a vaccine against colorectal liver metastases. (28th May 2012) - Dave, R; Errington-Mais, F; Kirn, D; Toogood, G; Melcher, A
Abstract : Introduction: Liver resection for colorectal liver metastases (CRLM) from colorectal cancer (CRC) has a 50% 5-year survival rate. However, recurrence rates are reported as 50% within 2 years. Thus, there is a need for a further treatment modality that may induce long-lasting anti-tumoural activity. Virotherapeutics provides this by directly infecting and lysing tumour cells and inducing immune-mediated tumour cytotoxicity. Methods: Using a double-stranded enveloped pox virus backbone, a Vaccinia virus (VV), termed JX-594, has been genetically manipulated to encode for granulocyte macrophage colony stimulating factor (GM-CSF). Enzyme Linked Immunoabsorbent Assay (ELISA) was used to confirm production of GMCSF when CRC cell lines and primary CRLM tissue were infected with this VV. ELISA was also used to measure pro- and anti-inflammatory cytokines. Viral replication was investigated using a plaque assay technique and by directly infecting CRLM tissue with a related GFP-encoding VV. To demonstrate induction of the innate immune response we infected PBMCs with the virus and measured levels of degranulation of Natural Killer (NK) cells, and the cytotoxic ability when activated PBMCs were exposed to CRC targets. Results: JX-594 treatment results in up to 75% lysis of CRC cell lines in 96 h. VV can replicate in CRC cells (250-fold replication in 72 h), thus potentially spreading through a tumour cell population, magnifying its anti-tumour effect. VV is able to produce large quantities of GMSCF. This is a cytokine that can stimulate a variety of immune effector cells including dendritic cells, which can be recruited to the tumour environment. In our study, more than 50% of the NK cells become "armed" in response the viral treatment, with the release of granyzmes that can induce apoptosis of target tumour cells. These activated NK cells when exposed to CRC targets, result in a 40%–50% lysis of the tumour cells in 24 h. VV treatment can also cause the up-regulation pro-inflammatory cytokines around the tumour environment, and potentially suppress new vessel formation by inhibiting VEGF. Conclusion: Viral therapeutics holds promise as a novel treatment modality for treatment of disseminated malignancy, providing direct tumour-specific lysis and the induction of tumour-specific innate immunity. It has been shown to be safe for intravenous delivery and early studies show promising results. We propose that VV may provide an adjunct to liver resection for treatment of liver cancer, and we will soon embark on a multi-centre early phase trial, whereby VV will be administered intravenously pre-operatively. Competing interests: None declared.